Mastering digital transformation - Carayannis, Elias G.; Hanna, Nagy (Innovation, technology, and education for growth., 2016)
The information and communication technology revolution offers the promise of transforming economies and societies, and the risks of missing on a powerful techno-economic revolution and wasting scarce resources without much developmental impact. Some countries have mastered the process of digital transformation, and continue to realize substantial economic benefits. Others made substantial investments in the ICT infrastructure, with marginal impact. What makes for these differences among countries? Nagy Hanna presents a systematic approach to integrate ICT into development policies and programs across sectors of economy and society. This book bridges the current disconnect between the ICT specialists and their development counterparts in various sectors so as to harness the ongoing ICT revolution to maximize development impact and minimize downside risks. Posing a holistic and strategic framework that draws on lessons learned across all sectors to guide national leaders and development practitioners interested in moving from vision to action, it is an important work for researchers and students of ICT who aim to pursue innovative, inclusive and sustainable development paradigms.